Intra-Arterial Verapamil Treatment in Oral Therapy–Refractory Reversible Cerebral Vasoconstriction Syndrome - Ospel, J.M.; Wright, C.H.; Jung, R.; Vidal, L.L.M.; Manjila, S.; Singh, G.; Heck, D.V.; Ray, A.; Blackham, K.A. (American Journal of Neuroradiology, 2019)
SUMMARY: Reversible vasoconstriction syndrome is a complex of clinical symptoms and angiographic findings, which, while having a mostly benign clinical course, has clinical and imaging overlap with more serious disorders such as vasculitis and aneurysmal SAH and itself includes a minority of patients with fulminant vasoconstriction resulting in severe intracranial complications. Endovascular options for patients with refractory reversible cerebral vasoconstriction syndrome include intra-arterial vasodilator infusion similar to therapy for patients with vasospasm after SAH. To date, only case reports and 1 small series have discussed the utility of intra-arterial vasodilators for the treatment of reversible cerebral vasoconstriction syndrome. We report an additional series of 11 medically refractory cases of presumed or proved reversible cerebral vasoconstriction syndrome successfully treated with intra-arterial verapamil infusion. Furthermore, we propose that the reversal of vasoconstriction, as seen on angiography, could fulfill a diagnostic criterion.IAintra-arterialRCVSreversible cerebral vasoconstriction syndrome